Hubungan bimbingan orang tua dan motivasi belajar terhadap hasil belajar matematika materi pecahan sekolah dasar - Mailani Muslimah; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The aim of this study 1) to know the correlation of parental involvement with mathematics academic achievement 2) to know the correlation between learning motivation and mathematics academic achievement  3) to know the correlation of parental involvement and learning motivation with mathematics academic achievement. The study uses a survey method. The probability sampling technique is the technique used in this study. The subjects of this study were the fourth grade students in Laweyan district of 2021/2022. The results of the study showed that first, there was a correlation of parental involvement with mathematics academic achievement which has a Pearson Correlation value of 0.430 indicating that the correlation level is moderate. Second, there was a correlation of learning motivation with mathematics academic achievement which has a Pearson Correlation value of 0.434 indicating that the correlation level is moderate. Third, there was a correlation of parental involvement and learning motivation with mathematics academic achievement which has a Pearson Correlation value of 0.605 indicating that the correlation level is highKata kunci: parental involvement, learning motivation, mathematics achievement, and correlation